Electrochemical and computational study of gum exudates from Canarium schweinfurthii as green corrosion inhibitor for mild steel in HCl solution. Issue 6 (2nd November 2018) - Ameh, Paul Ocheje
ABSTRACT: The inhibition efficiency of the corrosion on mild steel in acid by Canarium schweinfurthii (CS) gum as inhibitor has been studied using chemical techniques (thermometric, gasometric, spectrophotometric and weight loss) and electrochemical techniques (electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP)). Scanning Electron Spectroscopy (SEM) was used to examine the surface morphology of mild steel samples both in the presence and absence of inhibitors at optimum conditions. Results obtained indicated that CS inhibited the corrosion of mild steel in HCl. The inhibition efficiency increases with increasing the inhibitor concentration but decreases with increasing the temperature. CS behaved as mixed type inhibitor retarding both cathodic and anodic reaction with high inhibition efficiency. Gas chromatography mass spectrometer (GCMS) spectrum of CS gum showed the presence of Nonacosane; 1-piperoylp; Stearic acid, 2-(hydroxymethyl)-2-nitropropane-1, 3-diol, Stigmasta-5, 22-dien-3-ol, dihex-5-en-2-yl phthalate, 9-octadecenoic acid, methyl ester, , 1-penta-decarecarboxylic and Oleic acid. Inhibition action of the gum gave a strong correlation with these phytochemicals in the gum. Phenomenon of physical adsorption was proposed for the inhibition and the process followed the Langmuir adsorption isotherm with very high negative values of the free energy of adsorption (ΔGads ). Both the chemical and electrochemical results are in good agreement with each other while the surface studies reveal the formation of a smooth, dense protective layer in the presence of inhibitor. Quantum chemical computations of parameters associated with the electronic structures of specific components of the gum supported their inhibiting potentials.